Filler Migration to the Orbit. (5th September 2020) - Hamed-Azzam, Shirin; Burkat, Cat; Mukari, Abed; Briscoe, Daniel; Joshi, Narish; Scawn, Richard; Alon, Eran; Hartstein, Morris
Abstract: Background: Dermal filler injections continue to grow in popularity as a method of facial rejuvenation. This increase in the number of injections performed has resulted in an increasing number of types of filler-related complications. Objectives: We report a series of cases where dermal filler injected in the face migrated to the orbit. Treatment methods and possible mechanisms of this newly reported complication are discussed. Methods: A retrospective, multicenter analysis was performed on patients with dermal filler migration to the orbit after facial filler injections. Results: Seven patients (6 females, 1 male; age range, 42-67 years) presented with orbital symptoms after filler injection and were subsequently found to have dermal filler in the orbit. Four out of 7 patients underwent orbitotomy surgery, 1 patient underwent lacrimal surgery, 1 patient had strabismus surgery, and 1 patient was treated with hyalurodinase injections. All patients have remained stable postoperatively. Conclusions: Orbital complications secondary to migrated filler may occur long after the initial procedure. Because the site of the complication is distant from the injection site, patients and physicians may not immediately make the connection. Furthermore, this may lead to unnecessary examinations and a delay in diagnosis while looking for standard orbital masses. Dermal fillers should therefore be considered in the differential diagnosis of patients presenting with new-onset orbital masses. Level of Evidence: 4: